2001
DOI: 10.1016/s0379-7112(01)00025-x
|View full text |Cite
|
Sign up to set email alerts
|

The who, what, where and why of waking to fire alarms: a review

Abstract: This review brings together several different strands of research: (i) The sleep arousal literature pertaining to auditory arousal thresholds (AAT), (ii) studies on factors affecting responsiveness to auditory signals during sleep, (iii) literature on responsiveness to smoke detector alarms during sleep and (iv) research on fire fatality statistics and victim characteristics. The review discusses the influence of age, sleep deprivation, signal frequency, background noise, hearing loss, time of night, stage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 34 publications
0
51
0
2
Order By: Relevance
“…Firstly, the modified methods of limits methodology meant that each volume level of a signal was not presented from silence, as would be the case when a smoke alarm signal sounds. Examination of the literature on awakenings to alarms [4,5] suggests that people may have lower AATs (i.e. wake up more readily at a certain decibel level) when that sound cuts in from silence.…”
Section: Experimental Versus Field Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the modified methods of limits methodology meant that each volume level of a signal was not presented from silence, as would be the case when a smoke alarm signal sounds. Examination of the literature on awakenings to alarms [4,5] suggests that people may have lower AATs (i.e. wake up more readily at a certain decibel level) when that sound cuts in from silence.…”
Section: Experimental Versus Field Settingsmentioning
confidence: 99%
“…It seems that sleep in ''normal'' populations is not in itself the major risk factor for fire fatality but that additional risk factors need to be present to substantially increase the chance of sleeping through an alarm. Studies of smoke alarms, auditory arousal and sleep [4] tells us that significant risk factors include being a child, being under the influence of hypnotics, being alcohol intoxicated, being hearing impaired, being sleep deprived and having high levels of background noise.…”
Section: Introductionmentioning
confidence: 99%
“…In order to estimate the percentage of those aged 60 to 69 years who would not awaken to a hallway high-pitched alarm (55-60 dBA alarm of 2000-4000Hz), Bruck (2001) extrapolated from ISO 7029-1984 data (International Organisation for Standardisation, 1984) on hearing threshold values. Using a derived 41-dBA difference between awake and asleep thresholds, it was estimated that at least 25% of people in their 60s would not awaken to such a hallway alarm.…”
Section: Impaired Adultsmentioning
confidence: 99%
“…Among the 6-64 yr olds 65% had ingested alcohol at the time of their death and of these, 40% were asleep. Secondary analyses of this data [6], based on some assumptions, concluded that among those that were asleep perhaps only about a quarter were asleep, able bodied and unimpaired (see Fig. 2).…”
Section: Sleep and Fire Statisticsmentioning
confidence: 99%
“…There is a considerable literature on sleep and arousal in different circumstances and studies in this area have been extensively reviewed previously [6,16]. This paper will mainly focus on those studies that have used fire cues or alarm signals to investigate awakening.…”
Section: Empirical Sleep Studiesmentioning
confidence: 99%